Contact Toxicity and Chemical Composition of Essential Oil of Acantholimon scorpius - Ardalan Pasdaran Lashgari, Abbas Delazar, Farriba Hesmati Afshar, Dena Parsa (Tabriz University of Medical Sciences, 2016)
Background: Plumbaginaceae plants family is a valuable natural insecticidal compound. This research focused on contact toxicity and chemical composition of essential oil obtained from Acantholimon scorpus. Methods: The essential oil from the aerial parts of A. scorpius was extracted by hydrodistillation method and tested for their toxicity against Oryzeaphilus mercator (Coleoptera: Silvanidae) and Tribolium castaneum (Coleoptera: Tenerbrionidae). Chemical compounds of the essential oil was analyzed by the gas chromatography-mass spectrometry (GC-MS) and gas chromatography-flame ionization detection (GC-FID). Results: The essential oil showed toxic effect on tested insects. This oil showed 90.0% mortality of O. mercator and 85.2% mortality of T. castaneum at a dose of 12 μl /l air after 48h of exposure. The constituents of this oil were identiﬁed, representing more than 82.9% of the total essential oil composition. Hexadecanoic acid, tetrahydrogeranyl acetone and oleic acid were the main compounds of the essential oil. Conclusion: According to the result the essential oil of A. scorpius showed a noticeable insecticidal activity in contact toxicity model.